Comparative recognition and enforcement : foreign judgments and awards - Stamboulakis, Drossos (Cambridge : Cambridge University Press, 2023)
This book provides the first detailed analysis of recognition and enforcement of foreign judgments and awards in civil and commercial matters from a transnational perspective. This perspective facilitates greater understanding of the present state of recognition and enforcement and offers insight into the establishment and operation of key modern instruments. This book represents a timely contribution, as instruments harmonising and promoting recognition and enforcement are increasingly being considered and implemented internationally. Many countries have recently reiterated their commitment to improving access to justice and have indicated an intention to sign one or both of the treaties designed to harmonise and promote recognition and enforcement of civil and commercial judgments internationally: the 2005 Choice of Court Convention or the 2019 Judgments Convention. This book is an essential resource for policymakers, scholars, and intergovernmental organisations to understand the nature and origin of recognition and enforcement approaches, as well as their application, interpretation, and future directions.
Introduction -- 'Global' recognition and enforcement approaches -- Uniform recognition and enforcement in Europe : the Brussels Model -- The Commonwealth Model and common law recognition and enforcement -- Comparative analysis of recognition and enforcement -- Overcoming hurdles to transnational recognition and enforcement -- Legal development : uniformity, divergence and evolution -- Towards 'transnationalised; recognition and enforcement -- Conclusion.
Title from publisher's bibliographic system (viewed on 10 Nov 2022).
Keywords: Judgments, Foreign